An Overall Interaction Concept for an alternative approach to steel members design. (August 2017) - Boissonnade, Nicolas; Hayeck, Marielle; Saloumi, Elsy; Nseir, Joanna
Abstract: The present paper focuses on a new, alternative design philosophy: the Overall Interaction Concept (O.I.C.). This concept, based on the well-established resistance-instability interaction and the definition of a generalised relative slenderness, was thought and built to i) improve actual design practice, ii) increase accuracy, iii) advance simplicity and consistency, and iv) provide a sound framework for computer-assisted resistance predictions. This paper first details the bases and features of the O.I.C. approach, and provides mechanical interpretations of its application steps. Comprehensive sets of results at the cross-sectional level are then presented, for both H-shaped and hollow sections. Ayrton-Perry-based χ - λ design relationships for hollow structural shapes are proposed and shown to lead to more accurate, consistent and safe resistances when compared to Eurocode 3 rules, in addition to being significantly simpler in application. As for the behaviour and response of members, numerous F.E. results are reported, demonstrating the potential of a χ - λ approach to successfully apply to members under combined load cases. Also, the challenging case of coupled instabilities is investigated, and the O.I.C. approach is showed to be very efficient and appropriate. Further developments towards the derivation of full O.I.C. procedures to steel members are currently under way.